Poglądy polityczne Żelaznego Kanclerza - Maciejewski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article is devoted to a critical analysis of Mariusz Kopczyński’s interpretation of Otto von Bismarck’s political thought. In the first part of the article the author recalls the earlier Polish attempts to describe the “Iron Chancellor”, noting that they concerned mostly his public activities. In the second part the author argues that although M. Kopczyński’s research did not bring about a “Copernican revolution” in the academic literature dealing with Bismarck, it did make a fresh contribution by describing the Chancellor as a political thinker.
Keywords: Bismarck, Otto von (premier Prus - 1815-1898); Niemcy; nacjonalizm; konserwatyzm; antysemityzm; Polska; kulturkampf